Comparison of Actinic Keratosis and Severity Index with Physician Global Assessment and Total Lesion Count and the Ability to Predict Skin Cancer - Acar, Ayda; Karaarslan, Isil (Dermatology Practical & Conceptual, 2022)
Introduction: Actinic keratosis (AK) is a known indicator for sun damage, and subsequent squamous cell cancer may develop. The actinic keratosis and severity index (AKASI) is a recently developed tool that can evaluate both field cancerization and AK severity.Objectives: We sought to evaluate if AKASI was a good predictor of cancer in AK patients and to compare AKASI with both the Physician Global Assessment (PGA) and total lesion count (TLC).Methods: Ninety patients with AK were included in the study. Each patient was examined, and AKs were scored with AKASI, PGA and TLC by 2 dermatologists. The AKASI, PGA and TLC values were compared between patients with skin cancer and patients without skin cancer.Results: Mean AKASI, PGA, and TLC scores were 4.9, 1.7 and 9 respectively. The patients with skin cancer had higher scores of AKASI, PGA and TLC compared to the patients without skin cancer (P = 0.022, P = 0.014, P = 0.005, respectively). AKASI, PGA and TLC were very strongly correlated with each other (P < 0.001). The AKASI threshold value for NMSC was determined to be 5.1.Conclusions: AKASI, PGA and TLC may be used in the assessment of the severity of AK in daily practice or studies and may be considered as valuable tools in determining high-risk patients and to choose treatment option. AKASI seems to have an advantage to give a numeric threshold value for skin cancer.